ANALISIS FAKTOR-FAKTOR MOTIVASI SISWA DALAM MENGIKUTI KEGIATAN EKSTRAKURIKULER PRAMUKA DI SD NEGERI 034 TARAIBANGUN - Ririn Oktavianis; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aims to determine the motivation of students in following extracurricular activities scout at Elementary School 034 Taraibangun. The research was conducted in January 2017. This research is a quantitative descriptive research on students' motivation to follow the extracurricular activities Scout in Elementary School 034 Taraibangun. The method used is survey method, while the data retrieval technique using attitude scale questionnaire. The attitude scale in this research is used to express students' motivation to follow the extracurricular activities Scout in Elementary School 034 Taraibangun. The population in this research is the students of Elementary School 034 Taraibangun. Sampling in this research using total sampling counted 90 student. The results of the research data showed the overall factors that motivate the students to follow the scout extracurricular activities exist in the category of being 34.44%, intrinsic motivation dominates the students to participate in extracurricular activities at Public Elementary School 034 Taraibangun scouts compared with extrinsic motivation. In the intrinsic motivation of students at the high category 34.44%, whereas extrinsic motivation is in the category was 38.89%. Based on the indicators of intrinsic motivation, indicators of need at the high category 43.33%, while the expectations indicator that the high category 38.89% and the indicator of interest at high category 52.22%. Based on the indicators of extrinsic motivation, family indicator is in the category was 44.44%, and in the indicator of environmental middle category 38.89%, and the reward indicatoris the category was 28.89%.Key Words: Motivation, Extracurricular, Scout